Association between autophagy and KRAS mutation with clinicopathological variables in colorectal cancer patients - Awi, Noel Jacques; Yap, Hooi Yeen; Subasri, A.; Low, John Seng-Hooi; Peh, Kaik-Boo; Peh, Suat Cheng *; Lee, C. S.; Teow, Sin Yeang * (College of Pathologists, Academy of Medicine Malaysia, 2021)
Autophagy is a host defensive mechanism responsible for eliminating harmful cellular components through lysosomal degradation. Autophagy has been known to either promote or suppress various cancers including colorectal cancer (CRC). KRAS mutation serves as an important predictive marker for epidermal growth factor receptor (EGFR)-targeted therapies in CRC. However, the relationship between autophagy and KRAS mutation in CRC is not well-studied. In this single-centre study, 92 formalin-fixed paraffin-embedded (FFPE) tissues of CRC patients (42 Malaysian Chinese and 50 Indonesian) were collected and KRAS mutational status was determined by quantitative PCR (qPCR) (n=92) while the expression of autophagy effector (p62, LC3A and LC3B) was examined by immunohistochemistry (IHC) (n=48). The outcomes of each were then associated with the clinicopathological variables (n=48). Our findings demonstrated that the female CRC patients have a higher tendency in developing KRAS mutation in the Malaysian Chinese population (p<0.05). Expression of autophagy effector LC3A was highly associated with the tumour grade in CRC (p<0.001) but not with other clinicopathological parameters. Lastly, the survival analysis did not yield a statistically significant outcome. Overall, this small cohort study concluded that KRAS mutation and autophagy effectors are not good prognostic markers for CRC patients.